2009
DOI: 10.1017/s0007123408000380
|View full text |Cite
|
Sign up to set email alerts
|

Troubles with Transposition? Explaining Trends in Member-State Notification and the Delayed Transposition of EU Directives

Abstract: EC directives must be transposed into the national legal order of the member states within a specified deadline. Although member states are obliged to notify their transposition measures, they often fail to comply with these deadlines. Distinguishing between domestic and EU-related factors, this study examines transposition failure and delay of EC directives from 1986 to 2002. Notification failure is found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
145
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(150 citation statements)
references
References 8 publications
4
145
0
1
Order By: Relevance
“…Further studies may therefore focus on this dimension of noncompliance. In all cases in which directives had to be implemented at federal state level, federalism delayed their transposition, which strongly supports previous findings (Haverland/Romeijn 2007;Linos 2007;König/ Luetgert 2009;Thomson 2010). In the case of Austria, we can therefore draw the conclusion that domestic factors, in particular, determined the implementation outcomes, irrespective of the voting behaviour in the Council.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Further studies may therefore focus on this dimension of noncompliance. In all cases in which directives had to be implemented at federal state level, federalism delayed their transposition, which strongly supports previous findings (Haverland/Romeijn 2007;Linos 2007;König/ Luetgert 2009;Thomson 2010). In the case of Austria, we can therefore draw the conclusion that domestic factors, in particular, determined the implementation outcomes, irrespective of the voting behaviour in the Council.…”
Section: Resultssupporting
confidence: 88%
“…Most studies found no relationship between the decision-making rule in the Council and compliance. One study concluded that a qualified majority vote constrained implementation, as the interests of member states could be overruled (König/Luetgert 2009), while another study described positive effects on the transposition resulting from qualified majority voting (Luetgert/Dannwolf 2009). …”
Section: Europeanisation and Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on EU level factors greater conflict between Member States, more legislative actors involved and qualified majority voting in the Council seem to increase the probability for timeliness (König et al 2005). Yet others place much emphasis on cross-sectoral variance which rests on typical characteristics of directives in the respective policy sectors ).…”
Section: Official Statistics On Transposition Notificationsmentioning
confidence: 99%
“…Nevertheless, the solution might not be in the "creation", but in the "respect" and "practice" of the current laws and a more efficient transposition of European Union directives. The implementation of European Union directives also varies in different countries 60 , and very often there are troubles in European Union directive transposition 61 that normally are delayed due to the lack of resources, competence, administrative ineffectiveness, lack of experience, political and administrative priority 62 . Sub-national interests may also delay the transposition and implementation of directives 63 .…”
Section: Local Stakeholders Responses To Urban Sprawlmentioning
confidence: 99%